Bidirectional regulation of adenosine-to-inosine (A-to-I) RNA editing by DEAH box helicase 9 (DHX9) in cancer. Issue 15 (18th May 2018) - Hong, HuiQi; An, Omer; Chan, Tim H M; Ng, Vanessa H E; Kwok, Hui Si; Lin, Jaymie S; Qi, Lihua; Han, Jian; Tay, Daryl J T; Tang, Sze Jing; Yang, Henry; Song, Yangyang; et al.
Abstract: Adenosine-to-inosine (A-to-I) RNA editing entails the enzymatic deamination of adenosines to inosines by adenosine deaminases acting on RNA (ADARs). Dysregulated A-to-I editing has been implicated in various diseases, including cancers. However, the precise factors governing the A-to-I editing and their physiopathological implications remain as a long-standing question. Herein, we unravel that DEAH box helicase 9 (DHX9), at least partially dependent of its helicase activity, functions as a bidirectional regulator of A-to-I editing in cancer cells. Intriguingly, the ADAR substrate specificity determines the opposing effects of DHX9 on editing as DHX9 silencing preferentially represses editing of ADAR1-specific substrates, whereas augments ADAR2-specific substrate editing. Analysis of 11 cancer types from The Cancer Genome Atlas (TCGA) reveals a striking overexpression of DHX9 in tumors. Further, tumorigenicity studies demonstrate a helicase-dependent oncogenic role of DHX9 in cancer development. In sum, DHX9 constitutes a bidirectional regulatory mode in A-to-I editing, which is in part responsible for the dysregulated editome profile in cancer.